Mimicking Sensory Adaptation with Dielectric Engineered Organic Transistors. Issue 48 (3rd October 2019) - Shen, Hongguang; He, Zihan; Jin, Wenlong; Xiang, Lanyi; Zhao, Wenrui; Di, Chong‐an; Zhu, Daoben
Abstract: Mimicking sensory adaptation with transistors is essential for developing next‐generation smart circuits. A key challenge is how to obtain controllable and reversible short‐term signal decay while simultaneously maintaining long‐term electrical stability. By introducing a buried dynamic‐trapping interface within the dielectric layer, an organic adaptive transistor (OAT) with sensory adaptation functionality is developed. The device induces self‐adaptive interfacial trapping to enable volatile shielding of the gating field, thereby leading to rapid and temporary carrier concentration decay in the conductive channel without diminishing the mobility upon a fixed voltage bias. More importantly, the device exhibits a fine‐tuned decay constant ranging from 50 ms to 5 s, accurately matching the adaptation timescales in bio‐systems. This not only suggests promising applications of OATs in flexible artificial intelligent elements, but also provides a strategy for engineering organic devices toward novel biomimetic functions. Abstract : An organic adaptive transistor (OAT) with an inbuilt dynamic charge trapping interface within the dielectric layer is demonstrated to be a versatile platform for biomimetic sensory adaptation applications. Its precisely regulated decay constant accurately matches the adaptation timescales in bio‐systems, suggesting OATs are promising candidates for the next generation of smart applications.